Kondo lattice heavy fermion behavior in CeRh2Ga2. (14th February 2017) - Anand, V K; Adroja, D T; Bhattacharyya, A; Klemke, B; Lake, B
Abstract: The physical properties of an intermetallic compound CeRh2 Ga2 have been investigated by magnetic susceptibility χ ( T ), isothermal magnetization M ( H ), heat capacity C p ( T ), electrical resistivity ρ ( T ), thermal conductivity κ ( T ) and thermopower S ( T ) measurements. CeRh2 Ga2 is found to crystallize with CaBe2 Ge2 -type primitive tetragonal structure (space group P 4/ nmm ). No evidence of long range magnetic order is seen down to 1.8 K. The χ ( T ) data show paramagnetic behavior with an effective moment μ e f f ≈ 2.5   μ B /Ce indicating Ce 3+ valence state of Ce ions. The ρ ( T ) data exhibit Kondo lattice behavior with a metallic ground state. The low- T C p ( T ) data yield an enhanced Sommerfeld coefficient γ = 130 ( 2 ) mJ/mol K 2 characterizing CeRh2 Ga2 as a moderate heavy fermion system. The high- T C p ( T ) and ρ ( T ) show an anomaly near 255 K, reflecting a phase transition. The κ ( T ) suggests phonon dominated thermal transport with considerably higher values of Lorenz number L ( T ) compared to the theoretical Sommerfeld value L 0 .